Renewable synthesis of MoO3 nanosheets via low temperature phase transition for supercapacitor application - Sankar, Amba K.N.; Kesavan, Lokesh; Saha, Bikash; Jyolsnaraj, M.K.; Mohan, S.; Nandakumar, P.; Mohanta, Kallol; Kvarnström, Carita (Springer Nature, 2025)
2D transition metal oxides have created revolution in the field of supercapacitors due to their fabulous electrochemical performance and stability. Molybdenum trioxides (MoO3) are one of the most prominent solid-state materials employed in energy storage applications. In this present work, we report a non-laborious physical vapor deposition (PVD) and ultrasonic extraction (USE) followed by vacuum assisted solvothermal treatment (VST) route (DEST), to produce 2D MoO3 nanosheets, without any complex equipment requirements. Phase transition in MoO3 is often achieved at very high temperatures by other reported works. But our well-thought-out, robust approach led to a phase transition from one phase to another phase, for e.g., hexagonal (h-MoO3) to orthorhombic (α-MoO3) structure at very low temperature (90 °C), using a green solvent (H2O) and renewable energy. This was achieved by implementing the concept of oxygen vacancy defects and solvolysis. The synthesized 2D nanomaterials were investigated for electrochemical performance as supercapacitor electrode materials. The α-MoO3 electrode material has shown supreme capacitance (256 Fg-1) than its counterpart h-MoO3 and mixed phases (h and α) of MoO3 (< 50 Fg-1). Thus, this work opens up a new possibility to synthesize electrocapacitive 2D MoO3 nanosheets in an eco-friendly and energy efficient way; hence can contribute in renewable circular economy.